2019
DOI: 10.1590/1678-5150-pvb-5922
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of virginiamycin for the control of periodontal disease in calves

Abstract: Periodontal diseases are multifactorial infectious processes caused by complexes of microorganisms, with damage to health, production, and animal welfare. The aim of the present study was to evaluate the efficacy of virginiamycin in the prevention and control of two early forms of periodontal disease: gingivitis and necrotizing gingivitis. Ten weaned calves, aged four to six months, were permanently kept in a single lot under the same rotational grazing regime in a newly reformed area of Panicum maximum. Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…The hypothesis that dietary factors are an important component that would act on dental conditions and systemic health has been reported in studies involving different animal species (Dutra et al 1993, Gawor et al 2006, Borsanelli et al 2017b, Campello et al 2019, including deer (Pérez-Barbería & Gordon 1998, Stimmelmayr et al 2006, Mackenzie et al 2011. In domestic ruminants, newly reformed pastures and new opening areas for livestock are recognized as risk factors for the prevalence of periodontal diseases (Döbereiner et al 1975, Dutra et al 1993, Ramos et al 2019. Ramos et al (2019) described the occurrence of periodontal diseases (gingivitis and necrotizing gingivitis) in cattle kept under grazing in areas of newly reformed pastures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothesis that dietary factors are an important component that would act on dental conditions and systemic health has been reported in studies involving different animal species (Dutra et al 1993, Gawor et al 2006, Borsanelli et al 2017b, Campello et al 2019, including deer (Pérez-Barbería & Gordon 1998, Stimmelmayr et al 2006, Mackenzie et al 2011. In domestic ruminants, newly reformed pastures and new opening areas for livestock are recognized as risk factors for the prevalence of periodontal diseases (Döbereiner et al 1975, Dutra et al 1993, Ramos et al 2019. Ramos et al (2019) described the occurrence of periodontal diseases (gingivitis and necrotizing gingivitis) in cattle kept under grazing in areas of newly reformed pastures.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the set of periodontal diseases involves a group of multifactorial infectious and inflammatory diseases with different types of clinical manifestations, whose etiology is associated with dysbiosis of the oral biofilm (Hajishengallis 2015, Kinane et al 2017. Clinical signs initially include an inflammatory gingival process (gingivitis), characterized by edema, hyperemia, spontaneous bleeding, or probing, which may induce necrosis (Logan et al 1995, Lyon 2005, Ramos et al 2019, or progression of periodontal involvement (Hajishengallis 2015, Shaw et al 2016. In sheep, periodontitis and odontogenic abscesses are associated with the use of newly cultivated forage (Silva et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several edema degrees cause submucosal spacing between collagen fibers in all sheep evaluated due to inflammation. Edema was a clinical sign that Ramos et al (2019) observed in calves with gingivitis. Döbereiner et al (1974) also observed this change in their study in cattle, in which they noticed that the collagen fibers were disorganized in mild to moderate intensity in the periodontal region.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics should not have contraindications for use and should not cause adverse reactions in the body after administration [ 13 ]. The primary task of the Kazakh production of probiotics intended to maintain and restore the symbiotic microbiocenoses of humans and animals is the production of competitive drugs that are not inferior in their consumer properties to similar imported drugs [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%